2018
DOI: 10.1177/0093854818772320
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Relationship Between Social Ties, Prison Visitation, and Recidivism

Abstract: Studies find inmates who receive visits while incarcerated are less likely to recidivate upon release, especially when visits are from spouses and occur frequently throughout incarceration. Absent from these studies is measurement of the quality of an inmate’s relationships prior to incarceration, which may play a more significant role in criminal desistance than visitation itself. Longitudinal data from 205 incarcerated male and female adult offenders were used to test the mediating effects of visitation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 67 publications
(119 reference statements)
2
31
1
2
Order By: Relevance
“…Unsurprisingly, preconfinement support is also correlated with during-confinement support: Those who had support from each party preconfinement were more likely to receive visits from them. This is similar to recent work linking preconfinement relationship quality to receiving visits (Atkin-Plunk and Armstrong 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Unsurprisingly, preconfinement support is also correlated with during-confinement support: Those who had support from each party preconfinement were more likely to receive visits from them. This is similar to recent work linking preconfinement relationship quality to receiving visits (Atkin-Plunk and Armstrong 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Studies have aimed to address this potential selection bias with advanced techniques (e.g., propensity score matching; Mears et al 2012); however, these methods only control for bias on observables. Preconfinement support is rarely measured, yet is likely a key contributor to who is visited (e.g., Atkin-Plunk and Armstrong 2018). Additionally, our study contributes to the limited literature on the role of relationships and how support after confinement is interrelated across providers by examining whether it operates in tandem or fluctuates independently (see Pettus-Davis et al 2017).…”
Section: The Current Studymentioning
confidence: 99%
“…Not all studies, however, find beneficial effects of visits. Indeed, sometimes visitation has null effects on misconduct (Clark, 2001; Hensley, Koscheski, & Tewksbury, 2002; Jiang & Winfree, 2006; Lahm, 2008, 2009) and recidivism (Adams & Fischer, 1976; Atkin-Plunk & Armstrong, 2018). This diversity of results may follow, in part, from differences across studies in accounting for spuriousness.…”
Section: Prior Research On Visitationmentioning
confidence: 99%
“…This diversity of results may follow, in part, from differences across studies in accounting for spuriousness. For example, Atkin-Plunk and Armstrong (2018) found that controlling for the quality of pre-incarceration relationships reduced the effects of visitation to nonsignificance. Similarly, Cochran, Barnes, Mears, and Bales (2018) found that an instrumental variable approach to controlling for spuriousness eliminated the visitation effects evident in regression models that included relevant controls.…”
Section: Prior Research On Visitationmentioning
confidence: 99%
See 1 more Smart Citation